THE USE OF ORGANIC ACIDS AND ANORGANIK AS ACIDIFIER POSITIVE EFFECT ON PERFORMANCE OF PIGLET’S POST WEANING - Agung, I Gede Made Sunu Satwika Nur; Ardana, Ida Bagus Komang; Suada, I Ketut (Buletin Veteriner Udayana; Vol. 9 No. 1 Pebruari 2017, 2017)
The study aimed to determine effect of organic acid and anorganic (Orgacid™) as an acidifier in diet to body weight, feed concumption and feed convertion. The research used 24 pigs landrace male post lactation aged 30 days until 58 days. Feed stuffs used Charoen 550™ Made in PT.Charoen Pokphand Indonesia Tbk. The treatments given were: feed without Orgacid™, combination Orgacid™ 1g/kg feed, combination Orgacid™ 2g/kg feed, combination Orgacid™ 4g/kg feed. Variables measured were body weight, feed concumption, feed convertion. Data were subjected to analysis of variance. The result of the research showed that the addition of Orgacid™ 1g/kg to 4g/kg in feed did not significantly affected (P>0.05) to body weight, feed concumption and feed convertion.
Keywords: Pertambahan bobot badan, konsumsi pakan, konversi pakan, Orgacid™